Phone and Self: How Smartphone Use Increases Preference for Uniqueness - Song, Camilla Eunyoung; Sela, Aner (Journal of Marketing Research, 2023)
One of the most dramatic shifts in recent years has been consumers’ increased use of smartphones for making purchases and choices—but does using a smartphone influence what consumers choose? This article shows that, compared with using a personal computer (PC), making choices using a personal smartphone leads consumers to prefer more unique options. The authors theorize that because smartphones are considerably more personal and private than PCs, using them activates intimate self-knowledge and increases private self-focus, shifting attention toward individuating personal preferences, feelings, and inner states. Consequently, making choices using a personal smartphone, compared with a PC, tends to increase the preference for unique and self-expressive options. Six experiments and several replications examine the effects of personal smartphone use on the preference for unique options and test the underlying role of private self-focus. The findings have important implications for theories of self-focus, uniqueness seeking, and technology’s impact on consumers, as well as tangible implications for many online vendors, brands, and researchers who use mobile devices to interact with their respective audiences.